Rapid increase of syphilis in Tokyo: an analysis of infectious disease surveillance data from 2007 to 2016 - Yoshiyuki Sugishita; Aya Kayebeta; Kumiko Soejima; Mariko Yauchi (World Health Organization Regional Office for the Western Pacific, 2019)
The objective of this study was to examine the trends of primary and secondary syphilis in Tokyo between 2007 and 2016 using national infectious disease surveillance data. We analysed all 3269 cases reported during these 10 years. A statistically significant increase in cases was observed after 2010 with a more rapid rate of increase after 2014 mainly in urban areas in Tokyo. The notification rates per 100 000 population in 2010, 2014 and 2016 were 0.9 (n = 113), 2.2 (n = 295) and 8.7 (n = 1190), respectively. Domestic syphilis transmission was suspected in 92.6-99.3% of cases during the period 2007-2016. Until 2013, the increase was mainly observed among men who have sex with men (MSM); however, heterosexual transmission became more dominant and eventually surpassed transmission among MSM in 2015. In 2016, the notified cases of infections through heterosexual contact were 22.3 and 40.4 times higher in men and women, respectively, compared to those in 2010. The median ages of affected heterosexual men and women were 37 (interquartile range: 28-46) and 26 (interquartile range: 22-32) years, respectively. Reports of oropharyngeal lesions have been increasing among both men and women with syphilis. The number of congenital syphilis cases reported in Tokyo was 0 to 3 cases per year during the study period. More information and further analysis are needed to explain the reason for this increase.